The Impact of Metabolic Syndrome on Increased Risk of Thyroid Nodules and Size - Abdulbari Bener; Yaşar Özdenkaya; Cem Cahit Barışık; Mustafa Öztürk (SAGE Publishing, 2018)
Aim: The present research aimed to determine the relation between metabolic syndrome (MetS) and thyroid volume and nodule prevalence among Turkish population patients. Methods: This retrospective cohort study was carried on 850 patients between the ages of 20 and 65 who visited the diabetic, endocrinology, and general surgery outpatient clinics in the Mega Medipol and Medipol Hospital between January 2014 and December 2017. This study included sociodemographic information, body mass index (BMI), diabetes mellitus (DM), systolic (SBP) and diastolic (DBP) blood pressures, and clinical biochemistry results such as serum triglyceride, total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein (LDL) cholesterol, hemoglobin A1c (HbA1c), fasting blood glucose levels, thyroid-stimulating hormone (TSH), T3, T4, and other MetS parameters. Thyroid fine needle aspiration biopsy was suggested to patients whose thyroid nodules were greater than 1.00 cm. The definition and diagnostic of MetS used as proposed by the National Cholesterol Education Program-Third Adult Treatment Panel. Results: There were statistically significant differences between patients with thyroid nodules and those without regarding age, gender, BMI, physical activity, cigarette smoking, shisha smoking, family history of diabetes, hypertension, and thyroid. Meanwhile, statistically significant differences were found between with and without MetS for calcium ( P = .028), magnesium ( P < .001), potassium ( P < .001), fasting blood glucose ( P = .047), HbA1c ( P < .001), HDL ( P < .001), LDL ( P < .001), albumin ( P = .008), bilirubin ( P = .002), triglyceride ( P = .011), SBP ( P = .001) and DBP ( P = .011), TSH ( P = .005), T3 ( P < .001), and T4 ( P < .001). Furthermore, there were statistically significant differences between participants with and without thyroid nodules for calcium ( P < .001), magnesium ( P < .001), potassium ( P < .001), fasting blood glucose ( P = .010), HbA1c ( P = .019), HDL ( P < .001), LDL ( P = .012), albumin ( P = .002), bilirubin ( P < .001), triglyceride ( P < .001), SBP ( P < .001) and DBP ( P = .004), TSH ( P = .015), T3 ( P < .001), and T4 ( P < .001). Multivariate stepwise logistic regression analysis used for independent predictors for the presence of thyroid nodules which TSH ( P < .001), family history of thyroid and DM ( P < .001), age in years ( P = .025), DBP and SBP ( P < .001), BMI ( P = .014), HDL-C ( P = .034), and waist circumference (in cm; P = .044) were considered at higher risk as a predictors of thyroid with patients with MetS. Conclusion: The results of the current study confirm a strong positive association between MetS and thyroid nodules risk among patients with MetS. This study suggest that the patients with MetS can be considered as a marker to have moderately increased risk of future thyroid nodules and cancer. Meanwhile, MetS, obesity, and hyperglycemia could be a qualifiable and modifiable risk factor for thyroid nodules. The regularly glycemic control may be the most important treatment for the reduction of incidence or the prevention of thyroid.